2019
DOI: 10.24940/theijbm/2019/v7/i11/bm1911-044
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Disclosures and Firm Value of Commercial Banks Listed on the Nairobi Security Exchange, Kenya

Abstract: Accounting Disclosures and Firm Value of Commercial Banks Listed on the Nairobi Security Exchange, Kenya 1. Introduction and Background Over the last few decades, there has been an increase in the use of International Financial Reporting Standards (IFRS) and its predecessor the International Accounting Standards (IAS) in major corporations across the globe (Alfraih & Alanezi, 2015). According to the International Accounting Standards Board (IASB) (2014) more than 130 countries have adopted the use of the IFRS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Ahmed and Hamdan, 2015;Rubino et al, 2016;Yanti and Patrisia, 2019;Mishra and Kapil, 2018;Rossi et al, 2021) have demonstrated a positive relationship between the board size and the firm value. In the same vein, Weterings and Swagerman (2012), Kiharo and Kariuki (2018), Gerged andAgwili (2020), andNoja et al (2021) indicated that board size is positively and significantly associated with the firm value in the financial sector.…”
Section: Board Size and Firm Valuementioning
confidence: 87%
See 4 more Smart Citations
“…Ahmed and Hamdan, 2015;Rubino et al, 2016;Yanti and Patrisia, 2019;Mishra and Kapil, 2018;Rossi et al, 2021) have demonstrated a positive relationship between the board size and the firm value. In the same vein, Weterings and Swagerman (2012), Kiharo and Kariuki (2018), Gerged andAgwili (2020), andNoja et al (2021) indicated that board size is positively and significantly associated with the firm value in the financial sector.…”
Section: Board Size and Firm Valuementioning
confidence: 87%
“…Consequently, the agency problem may occur due to the lack of convergence between majority and minority shareholders' interests (Vintila and Gherghina, 2014). Furthermore, Kiharo and Kariuki (2018) have demonstrated the negative relationship between ownership concentration and firm value of listed commercial banks in Kenya. Thus, based on what preceded, the following hypothesis is constructed: H4.…”
Section: Ownership Concentration and Firm Valuementioning
confidence: 99%
See 3 more Smart Citations